2012
DOI: 10.1128/jvi.05810-11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Inactivation of COPI Coatomer Separately Inhibits Vesicular Stomatitis Virus Entry and Gene Expression

Abstract: Viruses coopt cellular membrane transport to invade cells, establish intracellular sites of replication, and release progeny virions. Recent genome-wide RNA interference (RNAi) screens revealed that genetically divergent viruses require biosynthetic membrane transport by the COPI coatomer complex for efficient replication. Here we found that disrupting COPI function by RNAi inhibited an early stage of vesicular stomatitis virus (VSV) replication. To dissect which replication stage(s) was affected by coatomer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 67 publications
1
37
0
Order By: Relevance
“…Cureton and colleagues showed that COPI depletion also leads to defects in VSV entry (25), although there are differences between the two viruses in which particular steps are perturbed. Cureton and colleagues found that COPI depletion results in a decrease in viral fusion due to an ϳ40% decrease in VSV binding and a decreased rate of VSV internalization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cureton and colleagues showed that COPI depletion also leads to defects in VSV entry (25), although there are differences between the two viruses in which particular steps are perturbed. Cureton and colleagues found that COPI depletion results in a decrease in viral fusion due to an ϳ40% decrease in VSV binding and a decreased rate of VSV internalization.…”
Section: Discussionmentioning
confidence: 99%
“…The results from Cureton and colleagues suggest that indirect effects caused by long-term inactivation of COPI lead to general defects in the clathrin-mediated endocytosis pathway (25). VSV exclusively uses clathrin-mediated endocytosis for infection (27)(28)(29)(30)(31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported through a genome-wide siRNA screen the requirement of several host factors for VSV replication at various stages of the virus infection cycle (33). Among these, alanine deaminase-like (ADAL) protein was shown to be required for the VSV assembly/budding step, whereas GBF1, ARF1, and the proteins of the coatomer I (COPI) complex were required for VSV genome transcription and replication (33,48). Therefore, we examined if hnRNP K silencing affects the expression of some of these cellular factors.…”
Section: Requirement Of Hnrnp K In Vsv Infectionmentioning
confidence: 99%
“…Targeting lysobisphosphatidic acid (LBPA), which plays a role in cargo trafficking within endosomes, cholesterol mobilization and the formation of multivesicular bodies 86 has also been shown to inhibit influenza virus, vesicular stomatitis virus (VSV), Lassa Fever virus (LFV) and lymphocytic choriomeningitis virus (LCMV) 61,[87][88][89] . Depletion of components of the coat protein complex I (COPI) affects the entry of influenza virus and VSV and the endocytosis and vesicular transport of HCV and HIV [90][91][92] .…”
Section: Targeting Common Host-factors Used For Viral Replicationmentioning
confidence: 99%